Penerapan Model Pembelajaran Berbasis Proyek (Project-Based Learning) untuk Meningkatkan Pemahaman Konsep Ekonomi Moneter pada Mahasiswa - Muhammad Juwantho Lewa (CV. Rumoh Aceh Publishing, 2026)
This research is motivated by the low level of students' understanding of abstract monetary economics concepts, such as the monetary policy transmission mechanism, interest rates, and money supply control. The predominantly theoretical instruction makes it difficult for students to connect concepts with actual banking practices and real-world policy implementation. The aim of this study is to enhance students' understanding of monetary economics concepts through the implementation of the Project-Based Learning (PjBL) model. This study employed a Classroom Action Research (CAR) method conducted in two cycles. The research subjects were 32 students in the 4th semester of the Economic Education Department, FKIP, Universitas Halu Oleo. Data collection techniques included concept understanding tests, observation sheets, and student response questionnaires. The results showed that the implementation of PjBL significantly improved students' understanding of monetary economics concepts. In Cycle I, the average score of concept understanding reached 70.8 with a mastery rate of 65.6% (21 out of 32 students), which increased in Cycle II to 82.5 with a mastery rate of 90.6% (29 out of 32 students). The projects, which consisted of monetary policy simulation and analysis of banking interest rate data, proved effective in helping students understand the monetary policy transmission mechanism in a concrete manner. This study concludes that the PjBL model is effective in improving students' understanding of monetary economics concepts and can be recommended as an alternative instructional model for monetary economics courses at the Economic Education Department, FKIP, Universitas Halu Oleo.